2014
DOI: 10.1242/dev.091165
|View full text |Cite
|
Sign up to set email alerts
|

The expression of Y-linked Zfy2 in XY mouse oocytes leads to frequent meiosis 2 defects, a high incidence of subsequent early cleavage stage arrest and infertility

Abstract: Outbred XYSry- female mice that lack Sry due to the 11 kb deletion Srydl1Rlb have very limited fertility. However, five lines of outbred XYd females with Y chromosome deletions YDel(Y)1Ct-YDel(Y)5Ct that deplete the Rbmy gene cluster and repress Sry transcription were found to be of good fertility. Here we tested our expectation that the difference in fertility between XO, XYd-1 and XYSry- females would be reflected in different degrees of oocyte depletion, but this was not the case. Transgenic addition of Yp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 48 publications
1
37
1
Order By: Relevance
“…Such XY females would be expected to have very limited fertility, based on what is known from studies on the deleterious effect of expression of Y-linked genes in oocytes on meiosis and early embryonic development, in XY Sry -female mice (Vernet et al 2014b). Also in X * Y female wood lemmings (more closely related to the Ellobius genus), whereby a modified X * dominantly induces female differentiation, the oocytes are almost invariably X * X * due to a double nondisjunction event in oocyte precursors Winking et al 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Such XY females would be expected to have very limited fertility, based on what is known from studies on the deleterious effect of expression of Y-linked genes in oocytes on meiosis and early embryonic development, in XY Sry -female mice (Vernet et al 2014b). Also in X * Y female wood lemmings (more closely related to the Ellobius genus), whereby a modified X * dominantly induces female differentiation, the oocytes are almost invariably X * X * due to a double nondisjunction event in oocyte precursors Winking et al 1981).…”
Section: Discussionmentioning
confidence: 99%
“…XYF on a B6 background are almost always sterile (PSB unpublished data), although on the MF1 outbred background, they do breed [54, 55]. Using the MF1 strain, it has been shown that it is a combination of a markedly reduced oocyte pool together with the expression of the Y-encoded transcription factor ZFY2 in the oocytes leading to impaired development of embryos prior to implantation, which severely limits the fertility [55].…”
Section: Important Caveats Relating To the Fcg Crossmentioning
confidence: 99%
“…XYF on a B6 background are almost always sterile (PSB unpublished data), although on the MF1 outbred background, they do breed [54, 55]. Using the MF1 strain, it has been shown that it is a combination of a markedly reduced oocyte pool together with the expression of the Y-encoded transcription factor ZFY2 in the oocytes leading to impaired development of embryos prior to implantation, which severely limits the fertility [55]. Nevertheless, estrous cycle data collected in association with an FCG behavioral study [56] revealed that estrous cycles are still present in ~85–90% of MF1 XYF at 6–8 months of age (William Davies, personal communication), demonstrating that the majority of XYF ovaries are hormonally competent.…”
Section: Important Caveats Relating To the Fcg Crossmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, these XY female mice exhibit an anatomically female phenotype with ovary formation; however, they are generally infertile, exhibiting extensive loss of germ cells in the ovary except in a few cases comprising hybrid strains (Kato et al, 2013;Lovell-Badge and Robertson, 1990;Mahadevaiah et al, 1993;Park and Taketo, 2003;Taketo, 2015;Vanderhyden et al, 1997;Vernet et al, 2014b;Wang et al, 2013). Overall, it is evident that XY females form well-constructed foetal gonads consisting of sites of cyst formation, pregranulosa cells, and oogonia.…”
Section: Introductionmentioning
confidence: 99%